Visual health prevalence study in a school population in Bogotá, Colombia 2000 - Hernández Luna, Clara Patricia (Universidad de La Salle. Revistas. Ciencia y Tecnología para la Salud Visual y Ocular., 2003)
The visual deficiencies in schoolchildren can imply learning problems and a delay in psychosocial development. Due to lack of information in this area in the District a descriptive type of study was conducted having as its objective to determine the prevalence of visual‐ocular alterations, in a sample of 1.250 children from 5 to 14 years of age in public and private schools in Bogota. Forty two (42%) percent of schoolchildren presented some degree of deficiency in the following were the results: hypermetry (59.2%), astigmatism (28.2%), myopia (4.0%) and emetropy (9.0%). Among children that presented a deficit of AV, 9.6% used optic correctives. Among those that represented some degree of AV deficit and didn´t use eyeglasses at the moment of the exam: 62% came from public schools and 38% from private school. It is necessary to identify the visual health problem and to review the intervention strategies given the positive impact of the solution that may generated, especially in the schoolchildren.